A study on electronically controllable beamforming monopole antenna for telecommunication applications. Issue 4 (4th March 2023) - Alkurt, Fatih Ozkan; Unal, Emin; Palandoken, Merih; Altintarla, Gizem; Abdulkarim, Yadgar I.; Hasar, Uğur Cem; Karaaslan, Muharrem
ABSTRACT: The design, analysis, and prototyping of an electronically controllable beamforming monopole antenna (ECBMA), which could be a good candidate for ceil-mounted wireless telecommunication systems, are reported. The proposed ECBMA targeting the 2.45 GHz center frequency is based on the 'on-off' ground reflectors, which are connected to the main ground layer by twelve RF switches to implement digital logic states. There are twelve ground reflectors symmetrically positioned over azimuthal angle direction in the ECBMA structure controlled by RF switches and a microcontroller unit, thus resulting in a pattern change when the states of the switches change logically. The designed ECBMA has the following three main features. First, it has a good and stable reflection coefficient (S11) characteristic at the 2.45 GHz centre frequency. Second, it has a wideband characteristic between 2.15 and 2.85 GHz (700 MHz operational bandwidth). Third, it has the capability to create single, double, or multi-beam characteristics (multi-purpose) which is a highly desired feature in many modern wireless communication systems mainly suitable for indoor applications. The prototype of our ECBMA is fabricated, and the performance analysis is investigated experimentally and S11 and radiation characteristics have good performance and are in good agreement with the simulation results. The proposed ECBMA has a good candidate for wireless telecommunication purposes such as WLAN, ISM, Wi-Fi, Bluetooth and other RF peripherals like indoor applications.